Differences in acute retroviral syndrome by HIV-1 subtype in a multicentre cohort study in Africa. (28th November 2017) - Sanders, Eduard J.; Price, Matthew A.; Karita, Etienne; Kamali, Anatoli; Kilembe, William; Bekker, Linda-Gail; Lakhi, Shabir; Inambao, Mubiana; Anzala, Omu; Fast, Patricia E.; Gilmour, Jill; Powers, Kimberly A.
Abstract : Objective: Symptoms of acute retroviral syndrome (ARS) may be used to identify patients with acute HIV-1 infection who seek care. ARS symptoms in African adults differ by region. We assessed whether reporting of ARS was associated with HIV-1 subtype in a multicentre African cohort study representing countries with predominant HIV-1 subtypes A, C, and D. Methods: ARS symptoms were assessed in adults enrolling within 6 weeks after the estimated date of infection in an acute and early HIV-1 infection cohort study. HIV-1 subtype was determined by POL genotyping. We used log-binomial regression to compare ARS symptom prevalence among those with subtype A vs. C or D, adjusting for sex, time since enrolment, and enrolment viral load. Results: Among 183 volunteers ascertained within 6 weeks after estimated date of infection, 77 (42.0%) had subtype A, 83 (45.4%) subtype C, and 23 (12.6%) subtype D infection. Individuals with subtype A were 1.40 (95% confidence interval: 1.17, 1.68) times as likely as individuals with subtypes C or D to report any ARS symptoms; each individual symptom other than rash was also more prevalent in subtype A than in subtype C or D, with prevalence ratios ranging from 1.94 (1.40, 2.70) for headache to 4.92 (2.24, 10.78) for lymphadenopathy. Conclusion: Individuals with subtype A were significantly more likely than individuals with subtypes C or D to report any ARS symptoms. HIV-1 subtypes may help explain differences in ARS that have been observed across regions in Africa, and may impact the yield of symptom-based screening strategies for acute HIV infection detection. Abstract : Supplemental Digital Content is available in the text